Documenting traditional knowledge in relation to climate change and its effects in Tr'ondëk Hwëch'in traditional territory - Winton, Alexandra; Neufeld, David; Neufeld, Erin; McLeod, Georgette; Olson, Jackie; Friendship, Katelyn; Roburn, Shirley; Parsons, Sue; Hume, Trish (Canadian Cryospheric Information Network, 2016)
Tr'ondëk Hwëch'in is a self-governing First Nation that signed a Final Agreement with the Yukon Government and Canada in 1998. Tr'ondëk Hwëch'in offers a variety of year-round programming to the community of Dawson City, Yukon and many of these programs are supported by information collected through oral history interviews and the documentation of traditional knowledge. Our IPY project involved multiple phases, including field research, oral history interviews, community mapping, and academic partnerships. Other important aspects of this project included training for youth, and increasing local awareness about climate change. Over a period of nearly two years, the Tr'ondëk Hwëch'in Heritage Department conducted over forty oral history interviews with traditional and local knowledge holders within the communities of Dawson City, Yukon; Fort McPherson, Northwest Territories; and Eagle, Alaska. We incorporated climate change education into our culture camps and regular heritage programming, and developed traditional knowledge collection kits, allowing local youth to interview their elders about climate change. These interviews provide a solid baseline of information on how climate change is occurring in the North, and how it is affecting people¿s lifestyles and culture. The information collected has already been useful for integration into other research projects in Dawson City and in other northern communities. Some of the themes that arose from our research were: warmer winter temperatures of 5-10 degrees, which affects trappers (furs not primed) and ice road conditions, and creates a change in the lifestyle and psyche of a northerner; increasing brush and vegetation growth - not only thicker, but in higher altitudes and further north (this may create more food for animals such as moose, but could choke out other plants, such as lichens for caribou, and makes travel more difficult in the bush); a one to two week shift in animal mating/rutting seasons later into the fall, affecting hunting seasons, and quality of meat; new species such as cougar, deer, some birds and unidentified insects; melting permafrost resulting in large frost slumps, and erosion, which affects travel and gathering abilities, water quality and land value; declining numbers and quality of local salmon stocks, which has serious consequences for health, income and lifestyle; and less predictable weather, which can erode confidence in traditional knowledge and traditional knowledge holders. : Purpose: The rationale for this project was to gain local traditional knowledge from people who are directly affected by climate change in the North. Many of these individuals are elders and they will not be around forever - their knowledge is priceless. These individuals have observed changes in lifestyles, culture, traditions, natural resources and infrastructure, over a very long period of time. This information can be extremely useful in helping to determine what northerners value. It will also be of assistance in developing potential strategies for adapting to the impacts of climate change in the North. This project also helped to maintain the oral tradition of the Tr'ondëk Hwëch'in by encouraging the sharing of stories and observations, and by involving youth in the actual documentation of the traditional knowledge. The information collected will address the impacts of climate change on resources, culture, species, weather, infrastructure, etc., and it will be useful in developing baseline levels for comparison with future observations. : Summary: For most of the past decade, many northern communities have been experiencing the effects of climate change. As the impact of climate change becomes increasingly prevalent across the North, this may change the lifestyles of Aboriginal people who reside there. This project focuses on documenting traditional knowledge as it relates to climate change in the territory of the Tr'ondëk Hwëch'in First Nation. The resulting insights will provide perspective on what Aboriginal people in northern communities value and may help in developing strategies to adapt and cope with a changing environment.